Oscillation and asymptotic behavior of odd-order delay differential equations with impulses - Chen, F. (Нелінійні коливання, 2012)
The oscillation of solutions for a class of odd order nonlinear differential equation with impulses is considered and some sufficient conditions for oscillation of solutions are obtained, which improve and popularize some results in parts of the relative references. Two examples are given to illustrate the obtained results and one of them shows that not only delay but also impulses play a very important role in giving rise to the oscillations of equations. Розглянуто коливання розв’язкiв класу нелiнiйних диференцiальних рiвнянь з iмпульсною дiєю та отримано певнi достатнi умови коливання розв’язкiв. Отриманi результати покращують та роблять доступнiшими деякi результати, що отриманi у вiдповiдних цитованих роботах. Розглянуто два приклади, що iлюструють отриманi результати. Один iз них показує, що iмпульсна дiя вiдiграє велику роль у виникненнi коливань розв’язкiв.